Circumstances of religious conversion and motives for altruistic behaviour of the adepts of Orthodoxy: features of interrelation (based on the study «Typology of religiosity in the modern Belarus») - Karassyova, Svetlana G.; Shkurova, Elena V.; Plaunik, Natalia K. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
he article contains results of interpretation with the help of concepts of psychology of separate elements of the all-republican interdisciplinary study «Typology of religiosity in the modern Belarus». Within a group of respondents declaring affiliation to Orthodoxy, we saw features of interrelation of the circumstances of religious conversion and motives for altruistic behaviour of a religious person.